The use and benefits of e-technology business applications - Ledwaba, N. F.; Pelser, G. P. J.; Fatoki, O. O. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The paper investigates the use of and resultant benefits of e-business applications within the Capricorn District Municipality in the Limpopo Province. E-business applications are components of e-business such as e-commerce, and e-marketing which enable firms to perform their day-to-day activities with their partners and target market for developing and delivering value proposition to a firm's customers. The study uses the quantitative method to analyse the use and the benefits of e-business. Exploratory and descriptive research will be utilised to determine the use of e-business applications by businesses. A sample size of 330 businesses was used. The questionnaire was used for a pilot study conducted to improve the validity. The Cronbach alpha test was conducted to ascertain the reliability of the research instrument. Data were collected through the use of self-administered questionnaires in a survey. SPSS was used for data analysis. The results showed a clear exposition of the use of e-business applications, and the benefits that businesses experience when using e-business applications. Businesses experience several benefits when utilising e-business in their operational processes of developing value propositions. Business applications have a high impact on the operational performance of value propositions. E-business applications are easy and useful to implement in a business and provide relative inexpensive options for SME enterprises. Recommendations to businesses are to utilise e-business applications so that they are able to create and deliver value propositions in an efficient and effective manner.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: E-business; E-business applications; Benefits of e-business; Electronic commerce; E-speak (Computer network technology)